MODEL IMPLEMENTASI NILAI-NILAI ISLAM DALAM FALSAFAH PI’IL PESENGGIRI MASYARAKAT LAMPUNG DI LABUHAN MARINGGAI - Heri Cahyono; Novi Rahmawati (AT-TAJDID, 2019)
Pesenggiri Pi'il is a philosophy of life that is used as a reference for the people of Lampung from generation to generation because of the values contained therein that can have an impact on community life relationships. However, in the current era er pi'il pesenggiri philosophy has begun to erode even forgotten, so that many people do not know and understand the true meaning of pesenggiri pi'il. The results of the study can be known Islamic values in the Pesenggiri Pi'il Philosophy through its elements namely adek nickname elements there are leadership values. The element of nyimah is the value of friendship, the value of courtesy, and the value of mutual respect. The blurring element is social values and intellectual values. And the sakai samabaian element has mutual values, and ta'wun values. The implementation of the Pesenggiri Pi'il Life Philosophy in Maringgai Village is still preserved.Keywords: Values, Islam, Pi'il Penengiri